XXXII Conference on Accounting in Business Management.Technologies in Accounting and Controlling held in Szczecin, May 8–9, 2025 - Jakub Karpiński; Oliwia Zielińska (Zeszyty Teoretyczne Rachunkowości, 2025)
The text contains a report on a scientific conference organised by the Chair of Accounting at the University of Szczecin from 8 to 9 May 2025 in Szczecin. The conference in the Accounting in Business Management cycle, under the motto, Technologies in Accounting and Controlling, addressed the latest technologies in improving accounting, reporting and controlling processes and their impact on the efficiency and innovation of business units. Plenary sessions featured discussions between renowned representatives from business and academia. In parallel, a dozen scientific posters were presented during the poster session. The conference provided a platform for the integration of the scientific community and practitioners, creating a space for a multidimensional discussion on the directions of development and the future of technology in this field.